Robyn C. Spencer, The Revolution Has Come: Black Power, Gender, and the Black Panther Party in Oakland: (Durham, NC: Duke University Press, 2016), 280pp, £20.00 / 24.95. (July 2017) - Grant, Nicholas
Abstract : Robyn C. Spencer's politically timely and eminently engaging history of the Black Panther Party (BPP) is a must read for anyone interested in Black Power and the history of the African American freedom struggle more broadly. Published on the fiftieth anniversary of the BPP's founding, The Revolution Has Come breaks new ground by presenting a wealth of original source material that sheds new light on the organizational development and the ideological outlook of the Panthers in Oakland.